2022
DOI: 10.1111/ddi.13585
|View full text |Cite
|
Sign up to set email alerts
|

Are species more harmful in their native, neonative or alien range? Insights from a global analysis of bark beetles

Abstract: Aim: Anthropogenic environmental modifications such as climate or land-use change are causing species to move on their own beyond their native ranges. As this phenomenon will increase in the near future, it is crucial to determine whether rangeexpanding species, or neonatives, are more or less likely than native and alien species to impact their recipient ecosystems. Here, we compared impact magnitudes of bark beetle species from their native, neonative and alien ranges, simultaneously. Location: Global. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 173 publications
0
8
0
Order By: Relevance
“…They found that origin was not a strong predictor of environmental impacts for bamboos. Forgione et al (2022) also used EICAT to evaluate the impact of 20 species of bark beetles (Insecta: Curculionidae) at a global scale. Their analysis suggests that bark beetles, like other species that are keystone and abundant in their native ranges, have generally lower impacts when introduced to novel environments due to biotic resistance or lack of pre-adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that origin was not a strong predictor of environmental impacts for bamboos. Forgione et al (2022) also used EICAT to evaluate the impact of 20 species of bark beetles (Insecta: Curculionidae) at a global scale. Their analysis suggests that bark beetles, like other species that are keystone and abundant in their native ranges, have generally lower impacts when introduced to novel environments due to biotic resistance or lack of pre-adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this information, we conducted the first comparison of the negative impact of native and introduced populations of a taxonomic group of terrestrial vertebrates using EICAT, and we tested the hypothesis that introduced species have greater environmental impacts than native species, that is, that origin status influence the magnitude of environmental impact. We found only three recent previous studies that used this score system to perform this type of comparison and test this hypothesis: 1) Canavan et al (2019) with bamboos (Poaceae: Bambusoideae) species, 2) Henry and Sorte (2022) with 39 marine species (including plants, invertebrates, fish, a protist and a bird) and 3) Forgione et al (2022) with bark beetles (genus Dendroctonus).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maladaptive hyper-virulence, for example, whereby pests quickly kill hosts, could theoretically increase pest prevalence in the short term but reduce pest prevalence in the long term, as available living hosts become rarer. While non-native pests may be most likely to be out of adaptive equilibrium with their hosts, there is as yet only limited evidence that they have systematically higher impacts on hosts than native pests [43,44].…”
Section: Plos Biologymentioning
confidence: 99%
“…'assisted migration' (cf. Hällfors et al, 2014;Pereyra, 2020)], these populations can cause ecological disruptions once established (Forgione, Bacher & Vimercati, 2022), but might simultaneously require protection given threats in their native ranges (Essl et al, 2021b;Forgione et al, 2022). The conundrum arises from the origin of environmental or climatic changes, which might also be considered anthropogenic, thereby blurring the distinction between 'neonative' and 'non-native'.…”
Section: Separating Ideology From Terminologymentioning
confidence: 99%